Pengaruh Ortografi Terhadap Interferensi Sintaksis Bahasa Arab Dalam Bahasa Indonesia oleh Mahasiswa Pendidikan Bahasa Arab IAIN Kediri - Zahroini, Alfi Lutfiana (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
Interference is one of the problems faced by Arabic language learners, because it has a negative impact on the practice of Arabic language skills. The emergence of interference is caused by the low grammatical ability of Arabic language learners, especially syntax, so that the structure of the first language, namely Indonesian, dominates Arabic without realizing it. So the orthographic system is one way to find and overcome various Arabic syntactic interference errors in Indonesian. This study aims to describe the effect of the orthographic system on Arabic syntactic interference in Indonesian and the elements of Indonesian syntactic interference in the Arabic language skills of students of the Arabic Language Education Study Program IAIN Kediri. This research is a descriptive qualitative research. The main data in the form of Arabic writing of students, then analyzed using the method of comparing the sentence structure of Arabic and Indonesian. Keywords: Interference, syntax, Indonesian, orthography